A Study of Histamine H2 Antagonists Effect on Survival Rate in Colorectal and Gastric Cancer Patients: A Meta-Analysis - Zhian Zarangan, Farahnaz; Shirdel, Ahmadreza; Moazzen, Nasrin; Amirabadi, Amir (Novelty in Biomedicine, 2025)
Background: Histamine H2 antagonists (H2RAs) are hypothesized to inhibit suppressor T-lymphocyte function, with preliminary evidence from randomized trials suggesting potential prolongation of survival in patients with operable and inoperable gastric and colorectal cancers. In this meta-analysis, we aimed to investigate the impact of these antagonists on the survival rate. Materials and Methods: The PubMed, Scopus, and Web of Science databases were searched through October 2024 to retrieve relevant papers. Study screening was performed using the RAYYAN software, and meta-analysis was executed with STATA version 18. Publication bias was assessed via Egger’s test, and study quality was evaluated using the Joanna Briggs Institute (JBI) critical appraisal tool. Graphical data were digitized using Plot Digitizer. Results: Initially, 181 articles were identified; after screening and applying inclusion criteria, six studies were included (three for colorectal cancer and three for gastric cancer). A random-effects model was employed, measuring standardized mean difference (SMD) in survival. In colorectal cancer patients, H2RAs were associated with a 5.4895% increase in survival compared to controls (95% CI: 0.49–10.47; P=0.03), predominantly driven by cimetidine. In gastric cancer, survival increased by approximately 2.38% in the treatment group, though not clinically significant. Conclusion: Current evidence suggests a potential survival benefit of H2RAs, particularly cimetidine, in colorectal cancer, but insufficient for gastric cancer. Larger, well-designed randomized controlled trials (RCTs) are required to confirm efficacy and optimize therapeutic protocols.